1997
DOI: 10.1097/00002820-199706000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral interventions to manage depression in patients with cancer: research and theoretical initiatives

Abstract: The incidence of depression is rising worldwide, possibly due to urban crowding and insufficient resources. This pandemic raises the possibility that disabling depression among patients with cancer will increase. Already, about one-third of patients with cancer present with depression. Although many progressive cancer centers are instituting psychooncology services, the projected decline in numbers of psychiatrists in the coming decade suggests that these programs may flounder unless nurses are able to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…It is caused by the loss of the sense of normality owing to the disease and the side effects of the long-term treatment. Depression in children with cancer is often expressed as a feeling of sorrow and less often as anorexia and decrease in the mood for activities (Cavusoglu 2001;Lovejoy & Matteis 1997;Von Essen et al 2000).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It is caused by the loss of the sense of normality owing to the disease and the side effects of the long-term treatment. Depression in children with cancer is often expressed as a feeling of sorrow and less often as anorexia and decrease in the mood for activities (Cavusoglu 2001;Lovejoy & Matteis 1997;Von Essen et al 2000).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…scores to indicate cases of low (= 8), medium (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and high (!20) levels of distress have been recommended.…”
Section: The Impact Of Event Scale (Ies)mentioning
confidence: 99%
“…Maguire [12] has suggested that nurses should be educated in techniques to relieve psychosocial problems. According to Lovejoy and Matteis [13], nurses trained in cognitive-behavioural skills should take an active role in preventing and managing cancer-related depression.…”
Section: Introductionmentioning
confidence: 99%
“…[35] BDT'nin davranışsal yönü hayattan alınan tadı ve memnuniyeti artırmak amacıyla gerçekçi hedefler belirleme ve günlük aktiviteleri planlamaya odaklanmıştır. [36] Davranış teknikleri çoğu hasta tarafından kullanılabilir ve genellikle kısa sürede rahatlama sağlar. Teknikler arasında, doktor için soru listesi oluşturma, hedefleri belirleme, etkinwww.cappsy.org lik planlama, rahatlama teknikleri ve günlük kullanarak faaliyet planlama vardır.…”
Section: Bireysel Bdtunclassified